Wise Behavior Models in Consuming Poor Farmers' Households - Putri Setyawati (CV. AFDIFAL MAJU BERKAH, 2022)
The background of this research is the existence of a household that is formed to maximize needs, welfare and happiness. Making the best decisions in economic matters is one of the skills that every household must have. This study uses a qualitative approach to the type of phenomenology. The location of this research is in Tlemang Village, Ngimbang District, Lamongan Regency. The selection of informants carried out in the study was carried out by various criteria using the purposive sampling technique. The data collection technique was carried out by interview, observation, and documentation with the informants who met the research criteria. Based on this research, it can be concluded that poor farmer households in Tlemang Village are wise in their consumption. It can be said that consumption is wise because households are not consumptive and manage harvests well, including recording expenses, having a priority scale in consumption, and budgeting funds. Farmer households in Tlemang Village feel prosperous when they can wisely manage their crops to meet their daily needs.